WEBVTT
00:00:00.480 --> 00:00:07.200
Solve 𝑥 squared minus four 𝑥 plus four equals zero by factorising.
00:00:08.520 --> 00:00:13.160
Factorising is the opposite or inverse of expanding or multiplying out parentheses.
00:00:13.800 --> 00:00:21.000
In this case, as the only common factor of the equation is one, we are going to need two parentheses.
00:00:21.600 --> 00:00:28.680
The first term in both of the brackets or parentheses must be 𝑥 as 𝑥 multiplied by 𝑥 is equal to 𝑥 squared.
00:00:29.440 --> 00:00:40.880
In order to work out the second term in both of the parentheses, we need to consider the general quadratic equation 𝑎 𝑥 squared plus 𝑏 𝑥 plus 𝑐 equals zero.
00:00:41.680 --> 00:00:51.840
If the coefficient of 𝑥 squared, 𝑎, is equal to one, then the two numbers have a product equal to 𝑐 and a sum equal to 𝑏.
00:00:52.560 --> 00:01:02.200
In our example, this means that the two numbers must have a product of four i.e., they have to multiply to give four.
00:01:02.720 --> 00:01:07.160
And they have to have a sum of negative four.
00:01:07.920 --> 00:01:13.840
We have four possible pairs of numbers that multiply or have a product of four.
00:01:14.440 --> 00:01:29.480
Two multiplied by two equals four, negative two multiplied by negative two is also equal to four, four multiplied by one is equal to four, and negative four multiplied by negative one also gives us an answer of four.
00:01:30.400 --> 00:01:34.920
Which of these four pairs of numbers gives us a sum of negative four when we add them?
00:01:35.560 --> 00:01:39.400
Well, two plus two is equal to positive four.
00:01:40.240 --> 00:01:43.600
So the top line cannot be our answer.
00:01:44.320 --> 00:01:50.120
Negative two plus negative two, however, does give us negative four.
00:01:50.760 --> 00:01:57.040
Carrying on, we can eliminate the bottom two lines as four plus one is equal to five.
00:01:57.680 --> 00:02:02.040
And negative four plus negative one is equal to negative five.
00:02:02.520 --> 00:02:09.240
This means that the numbers that are in our parentheses are negative two and another negative two.
00:02:09.760 --> 00:02:16.080
This leaves us with two brackets or parentheses 𝑥 minus two multiplied by 𝑥 minus two.
00:02:17.120 --> 00:02:20.800
We could expand this fully to get back to our original equation.
00:02:21.160 --> 00:02:24.360
But in this case, we’ve been asked to solve it.
00:02:25.000 --> 00:02:43.800
As 𝑥 minus two multiplied by 𝑥 minus two is equal to zero, one of these individual parentheses must also be equal to zero: either the first bracket 𝑥 minus two is equal to zero or the second bracket 𝑥 minus two is equal to zero.
00:02:44.560 --> 00:02:54.400
Adding two to both sides of these equations to balance them gives us answers of 𝑥 equals two or 𝑥 equals two.
00:02:55.440 --> 00:03:00.560
The majority of quadratic equations would have two different answers at this stage.
00:03:01.200 --> 00:03:09.680
However, since our brackets or parentheses were identical, we have ended up with just one solution: 𝑥 equals two.
00:03:10.440 --> 00:03:20.960
Therefore, the solution or answer to the equation 𝑥 squared minus four 𝑥 plus four equals zero is 𝑥 equals two.
00:03:21.920 --> 00:03:29.000
We could substitute this value back into the original equation to ensure we got an answer of zero.